Adsorção do fármaco diclofenaco em biocarvão de folhas de mandioca com uso de planejamento experimental - Schillo, Hellen Cristina Flor de Lima (2020)
The drug diclofenac sodium belongs to the class of non-steroidal anti-inflammatory drugs and has a very high consumption by the population due to its analgesic and antipyretic properties. Drug residues reach waters from several sources of contamination, and the main ones come from human and animal excretions, as well as drug disposal and industrial effluents. As water and sewage treatments cannot completely eliminate these drugs, it is necessary to develop new technologies that can remove them, since the existing ones are very expensive. Thus, adsorption comes as an alternative method of low cost and high efficiency. Biochar is a carbonaceous compound, with fine and porous granulation. It is a result from the incomplete burning of several biomasses. In addition, it is easy to be produced and an alternative to waste disposal, consequently, it has been widely applied as an adsorbent. Statistical tools application, such as a factorial design and the response surface, optimizes experimental conditions with the least number of possible experiments and reveals contributions of the technical variables to some analytical response in a mutual way. Thus, the experimental design and the response surface methodology were carried out aiming to reduce the number of experiments and obtaining the best conditions for the concentration reduction procedures of diclofenac sodium drug in solution after getting contact with the activated biochar of cassava leaves for 24 hours. Experiments were carried out using three factors at two levels, with three replications at the central point: pH (5.0; 7.0 and 9.0), mass of the biosorbent (25; 50 and 75 mg) and drug concentration (15; 27.5 and 40 mg/L). Biosorbent mass and drug concentration variables were significant and influenced negatively the response concerning the decrease on removing this drug amount, and positively concerning the increase on removing it as well, respectively. The optimum conditions were obtained with the lowest mass of biochar (25 mg) and the highest concentrations of this drug (40 mg/L). Kinetic behavior was evaluated using linear models of pseudo-first order and pseudo second order; and the model that best fitted the experimental data was the pseudo second order, whose qe value obtained by the model was 39.84mg/g. This result matched with the value obtained experimentally (39.77mg/g), whose relative error was 0.18%. The diclofenac removal by biochar occurred very quickly, since it reached 99% in 20 minutes. So, from this time on, it was considered that the system reached equilibrium, since the increase was no longer significant. The isotherm was also evaluated by Langmuir and Freundlich models, and Freundlich was the one that best fitted the experimental data. Therefore, the application of experimental design was essential to determine the conditions for maximum removal of diclofenac in aqueous solution. In addition, the biochar obtained from cassava leaf showed an excellent potential for diclofenac adsorption in aqueous solution and its promising results are a viable alternative in studies to remove this and other contaminating drugs in spring waters.